Steganography and Hiding Data with Indicators-based LSB Using a Secret Key - Saqer, W.; Barhoom, T. (Engineering, Technology & Applied Science Research, 2016)
Steganography is the field of science concerned with hiding secret data inside other innocent-looking data, called the container, carrier or cover, in a way that no one apart from the meant parties can suspect the existence of the secret data. There are many algorithms and techniques of concealing data. Each of which has its own way of hiding and its own advantages and limitations. In our research we introduce a new algorithm of hiding data. The algorithm uses the same technique used by the Least Significant Bit (LSB) algorithm which is embedding secret data in the least significant bit(s) of the bytes of the carrier. It differs from the LSB algorithm in that it does not embed the bytes of the cover data sequentially but it embeds into one bit or two bits at once. Actually it depends on indicators to determine where and how many bits to embed at a time. These indicators are two bits of each cover byte after the least two significant bits. The advantage of this algorithm over the LSB algorithm is the randomness used to confuse intruders as it does not use fixed sequential bytes and it does not always embed one bit at a time. This aims to increase the security of the technique. Also, the amount of cover data consumed is less because it sometimes embeds two bits at once.